Spontaneous rupture of a giant mature teratoma in the lateral ventricle: a case report - Xiao, Yong; Liu, Liang; Wang, Ran; Wang, Dong; Geng, Liangyuan; Hu, Xinhua; Liu, Yong; Qian, Chunfa; Zou, Yuanjie (Frontiers in Oncology, 2025)
We present the case of an adolescent female patient diagnosed with a ruptured lateral ventricle teratoma. Distinctive radiological and microscopic findings revealed floating oily globules within the ventricles and subarachnoid space. The spontaneous rupture of the teratoma may be attributed to age-dependent hormonal changes, which increase glandular secretion, cyst content volume, and intra-cystic pressure. The patient underwent gross total resection of the tumor, and the subsequent pathological examination confirmed the diagnosis of mature teratoma. Postoperatively, she was managed with routine follow-up without adjuvant chemotherapy or radiotherapy. During the 1-year follow-up period, the patient remained asymptomatic with no evidence of tumor recurrence. Based on this case, we recommend that gross total resection followed by close monitoring, without adjunctive chemotherapy or radiotherapy, can be an effective treatment strategy for patients with similar presentations.